MEASUREMENT OF SURFACE TENSION OF LIQUID ALLOWING FOR THE INFLUENCE OF CAPILAR OSCILATIONS OF IDLE DROP - Gorodetskay, Oksana; Stalchenko, Olexandre (Scientific Works of Vinnytsia National Technical University, 2015)
Instability and duration of drop transition in stationary state while measuring of surface tension by improved method of idle drop using step-wise growing voltage of electric field are analyzed.